Farmers' Perception of Agricultural Extension Worker Performance: A SEM-PLS Study on Garlic Farmers in West Miomaffo District, North Central Timor Regency, Indonesia - Marsianus Falo; Ody Wolfrit Matoneng; Oktovianus Tabenu (Politeknik Siber Cerdika Internasional, 2026)
government agricultural programs and smallholder farmers in eastern Indonesia. Despite the importance of this perception-performance nexus, no prior study has examined how internal and external factors of extension workers simultaneously influence farmer perceptions and behavioral change in the TTU garlic farming context. Objective: This study aims to develop a model of garlic farming extension programs and examine the internal and external characteristics of garlic farmers in West Miomaffo District. Methods: Data analysis techniques in this study used quantitative descriptive analysis, Spearman Correlation Test, and Structural Equation Modeling (SEM-PLS). This study employs a mixed-methods quantitative-descriptive design. A sample of 91 garlic farmers was drawn from 913 members across 48 farmer groups in West Miomaffo District using simple random sampling (10% of the population). Results: Farmer perceptions greatly influence the effectiveness of extension services and performance. Internal factors of agricultural extension workers (X1) have a positive and significant effect on the performance of agricultural extension workers (Y1). Internal factors of agricultural extension workers (X1) have a positive and significant effect on agricultural extension services (Y2). External factors (X2) have a positive and significant effect on agricultural extension worker performance (Y1). External factors (X2) have a positive and significant effect on agricultural extension services (Y2). Conclusion: The SEM-PLS model confirms that improving extension worker capacity and strengthening external support systems (infrastructure, incentives) are the key levers for improving farmer perceptions and agricultural outcomes in the TTU garlic farming sector.